2000
DOI: 10.1002/(sici)1099-1085(200003)14:4<679::aid-hyp966>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation in arctic proglacial lakes: Mittivakkat Glacier, south-east Greenland

Abstract: Abstract:Several sediment cores were collected from two proglacial lakes in the vicinity of Mittivakkat Glacier, southeast Greenland, in order to determine sedimentation rates, estimate sediment yields and identify the dominant sources of the lacustrine sediment. The presence of varves in the ice-dammed Icefall Lake enabled sedimentation rates to be estimated using a combination of X-ray photography and down-core variations in 137 Cs activity. Sedimentation rates for individual cores ranged between 0 . 52 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The coupling between the stratigraphy and the chronology based on two geo-chronological methods looked very promising (Figure 5). Similar good results between laminations and 210 Pb and 137 Cs derived age models for proglacial lacustrine sediment cores were observed in Icefall lake in the vicinity of the Mittivakkat Glacier (Hasholt et al, 2000). They interpreted the laminations as varves.…”
Section: Discussionsupporting
confidence: 72%
“…The coupling between the stratigraphy and the chronology based on two geo-chronological methods looked very promising (Figure 5). Similar good results between laminations and 210 Pb and 137 Cs derived age models for proglacial lacustrine sediment cores were observed in Icefall lake in the vicinity of the Mittivakkat Glacier (Hasholt et al, 2000). They interpreted the laminations as varves.…”
Section: Discussionsupporting
confidence: 72%
“…Despite several recent studies documenting elevated levels of FRNs in cryoconite in glaciers from Europe 5,9–17 , as far as we are aware no studies on elevated fallout contaminants in cryoconite have been conducted in North America. Furthermore, few studies have compared FRN concentrations in cryoconite to concentrations in fluvial sediments being actively transported in downstream proglacial rivers, to assess the broader environmental and ecological significance.…”
Section: Introductionmentioning
confidence: 85%
“…This would stand in contrast with the many studies that indicate that the formation of a proglacial lake generally results in a strong decrease in downstream sediment yield. For example, Hasholt et al (2000) estimated a trap efficiency of 90% for two lakes in south‐east Greenland, leading to considerably reduced sediment fluxes to the ocean. Geilhausen et al (2013) demonstrated that suspended sediment concentration decreased by up to 95% with the formation of a 0.2 km 2 proglacial lake in a 20 km 2 drainage area in Austria.…”
Section: Discussionmentioning
confidence: 99%